Patient satisfaction and survival rate of complete dentures done in the University of the Philippines College of Dentistry in 1996 - Vera Cruz, Eleanor M.
The study investigated the satisfaction rate of complete denture patients and the usage rate of complete dentures done by UP-College of Dentistry clinicians in 1996. The study aimed to determine the satisfaction rate of patients, survival rate of the dentures, and factors which contribute to failure of denture treatment. 30 interviews were accomplished. In terms of comfort in mastication. 30% replied that they were very comfortable, 23% comfortable. 23% okay, 7% not comfortable while 17% complained of pain. In terms of speech, 23% were able to speak very clearly, 34% spoke clearly. 23% okay, and 20% claimed not to speak clearly. In terms of retention, 37% replied that their dentures were very retentive. 20% retentive, 33% okay, and 10% complained of looseness. Regarding mucosal irritation or ulcerations, 47% never had any ulcerations brought about by the denture, 30% rarely, 10% had them once a month, and 13% had ulcerations once every week. Concerning esthetics, 30% found the appearance of their dentures very pleasing, 27% pleasing. 23% okay, 7% not pleasing, and 13% were unhappy because of their very ugh dentures. With regard to satisfaction rate, 38% patients were highly satisfied with their dentures. 17% moderately satisfied, 31% satisfied, and 14% moderately dissatisfied. The reasons for non-use of the dentures are: a) pain (60%). bi loss of the denture (10%), c) looseness of the denture (10%), d) dizziness (10%). and e) discomfort (10%). The mean satisfaction score of all 30 patients was 3.76 indicating moderate satisfaction. Seventy-three percent of subjects are currently using their dentures.